Supply Chain Ambidexterity and Supply Chain Performance: The Moderating Role of Firm Innovation. A Case Study of Some Selected Manufacturing Firms in The Greater Accra Region of Ghana (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study explored the relationship between supply chain ambidexterity, firm innovation, and supply chain performance among 161 manufacturing firms in Ghana. The main focus was to understand how firm innovation affects the link between ambidexterity and performance. Key findings include: (1) supply chain ambidexterity alone did not significantly impact performance, contradicting assumptions; (2) firm innovation capabilities, surprisingly, had a negative effect on performance, suggesting a need for better innovation alignment; and (3) innovation positively moderated the relationship between ambidexterity and performance, showing that combining innovation with ambidexterity can improve outcomes. Recommendations for managers emphasize the importance of aligning innovation strategies with supply chain goals and balancing exploration and exploitation activities. Future research should consider long-term studies, multi-region comparisons, and diverse data sources to increase validity. Overall, the study refines the understanding of how innovation and ambidexterity interact to enhance supply chain performance.